Certain classes of harmonic functions pertaining to special functions - G. Murugusundaramoorthy; K. Vijaya; K. Thilagavathi (Математичні Студії)
Making use of generalized Dziok-Srivastava operator we introduced a new class of complexvalued harmonic functions which are orientation preserving, univalent and starlike in the unit disc. We investigate the coefficient bounds, distortion inequalities, extreme points and inclusion results for the generalized class of functions.